The Effect of Tertiary Education Expansion on Fertility: A Note on Identification - Tushar Bharati; Simon Chang; Qing Li (Institute of Labor Economics (IZA), 2021)
We draw attention to two identification issues with previous studies that utilized tertiary education expansion to estimate the causal effect of education on fertility: (i) the mis-categorization of women past the usual college-entry age as "unexposed" to the expansion, and (ii) a possible violation of the exclusion restriction when using the expansion as an instrument for female education. We exploit the tertiary education expansion in Taiwan starting in 1996, with a novel focus on women past college-entry age, to document significant negative effects on the fertility of women as old as 30 at the onset of the expansion. We also show that the expansion lowered the fertility of women both with and without tertiary education, suggesting that the effect did not operate through education alone.
Keywords: I23; J13; 330; college expansion; marriage market; fertility; Taiwan